Genotoxic and Cytotoxic Effects of Dental Radiographic Modalities on Buccal Mucosal Cells in Children - Salman, Bahareh Nazemi; Rafieyan, Sona; Rahimipour, Kasra; Bayat, Narges (Journal of Child Science, 2023)
Dental radiography is an important diagnostic tool for the detection and assessment of the extent of dental caries and accurate treatment planning. There is no safe limit for X-ray exposure. The associated risks of X-ray exposure are higher in children due to a higher rate of cell proliferation in them, compared with adults. This study aimed to assess the genotoxic and cytotoxic effects of dental radiographic modalities on buccal mucosal cells in children. This interventional study evaluated 80 children between 3 and 12 years who required periapical, panoramic, bitewing, or bitewing plus panoramic radiography for treatment planning. Twenty eligible patients were assigned to each of the aforementioned four groups. Buccal mucosal cells were scraped bilaterally by a plastic spatula after complete rinsing of the oral cavity. The collected specimens were directly mounted on microscopic slides and after air-drying, they were fixed with 80% methanol and Giemsa stain. The cells were then inspected under a light microscope at 400x magnification for cytogenetic changes. Data were tabulated and analyzed by SPSS version 20 at a p < 0.001 level of significance. The results showed a significant increase in the frequency of karyolysis, karyorrhexis, and pyknosis in all four groups after dental radiography (p < 0.001). Also, the number of micronuclei significantly increased after panoramic plus bitewing radiography (p < 0.05). X-ray exposure in panoramic, periapical, bitewing, and bitewing plus panoramic radiographies can be cytotoxic, while bitewing plus panoramic radiography can be genotoxic in children as well.
Keywords: cytotoxicity; genotoxicity; X-ray; dental radiography; buccal mucosal cells